2011
DOI: 10.2298/ciceq100712060b
|View full text |Cite
|
Sign up to set email alerts
|

Some indicators of water quality of the Tamis river

Abstract: This paper shows the results obtained in field analysis performed at the Tamiš River, starting from the settlement Jaša Tomić (the border between Serbia and Romania) to Pančevo (the confluence of Tamiš into the Danube). The Tamiš is a 359 km long river rising in the southern Carpathian Mountains. It flows through the Banat region and flows into the Danube near Pančevo. Over the years, the water quality of the river has severely deteriorated and badly affected the environment and the river ecosystem. In situ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Considering the 50th percentile of total nitrogen content, the quality of the Karašica River surface water at sampling site 21012 can be described as good Gvozdić et al (2012) reported that the median concentration of nitrates in the River Drava surface water is relatively low compared to other rivers in western Europe (4.4-3.8 mg N/L) [27]. These values are similar to those obtained in the rivers in eastern Europe, for instance in the Danube and the Sava River (2.1-2.0, 1.6-0.95 and 1.3-1.2 mg N/L, respectively) [36,37].…”
Section: Nitrogen Compoundssupporting
confidence: 79%
“…Considering the 50th percentile of total nitrogen content, the quality of the Karašica River surface water at sampling site 21012 can be described as good Gvozdić et al (2012) reported that the median concentration of nitrates in the River Drava surface water is relatively low compared to other rivers in western Europe (4.4-3.8 mg N/L) [27]. These values are similar to those obtained in the rivers in eastern Europe, for instance in the Danube and the Sava River (2.1-2.0, 1.6-0.95 and 1.3-1.2 mg N/L, respectively) [36,37].…”
Section: Nitrogen Compoundssupporting
confidence: 79%
“…These parameters show physical, chemical and microbiological characteristics of the water and they are used in WQI (Water Quality Index) methodology (Scottish Development Department, 1976) in determining the overall water quality of the surface water. Based on the use of standard parameters for water characterization, the WQI sets the criteria for classification of surface water quality (Babović et al, 2011;Reza, & Singh, 2010;Banerjee & Srivastava, 2009;Sanchez et al, 2007;Kannel et al, 2007).…”
Section: Data Processing Methodologymentioning
confidence: 99%
“…On several shorter sections of the course, Tamiš meanders laterally, eroding higher relief, loess plain, and loess terrace, forming high riverbanks in the form of steep sections and slopes. Tamiš River is polluted by water supply facilities, fish ponds, industry, agriculture, and urban settlements [26]. Forty-seven samples were collected from the Tamiš River for this study.…”
Section: Study Areas and Methodsmentioning
confidence: 99%